Спростити вираз:
1) b¹ / ⁵ (⁵√b⁴ — ⁵√b⁻¹) / b² / ³ (∛b — ∛b⁻²)
(¹ / ⁵-пов

Спростити вираз:
1) b¹ / ⁵ (⁵√b⁴ - ⁵√b⁻¹) / b² / ³ (∛b - ∛b⁻²)
(¹ / ⁵-це подрібнена ступінь)
2) ∛a - ∛b / ⁶√a - ⁶√b

  •  1) \; \ frac {b ^ \ frac {1} {5} (\ sqrt [5] {b ^ 4} - \ sqrt [5] {b ^ {- 1}})} {b ^ {\ frac {2} {3}} (\ sqrt [3] {b} - \ sqrt [3] {b ^ {- 2 }})} = \ frac {b ^ {\ frac {1} {5} + \ frac {4} {5} - \ frac {1} {5}}} {b ^ {\ frac {2} {3 } + \ frac {1} {3} - \ frac {2} {3}}} = \ frac {b ^ {\ frac {4} {5}}} {b ^ {\ frac {1} {3} }} = b ^ {\ frac {4} {5} - \ frac {1} {3}} = b ^ {\ frac {7} {15}} = \ sqrt [15] {b ^ 7};

     2) \; \ frac { \ sqrt [3] {a} - \ sqrt [3] {b}} {\ sqrt [6] {a } - \ sqrt [6] {b}} = \ frac {(\ sqrt [3] {a}) ^ 2 - (\ sqrt [3] {b}) ^ 2} {\ sqrt [6] {a} - \ sqrt [6] {b}} = \ frac {\ sqrt [6] {a ^ 2} - \ sqrt [6] {b ^ 2}} {\ sqrt [6] {a} - \ sqrt [6 ] {b}} = \ frac {(\ sqrt [6] {a} - \ sqrt [6] {b}) (\ sqrt [6] {a} + \ sqrt [6] {b})} {\ sqrt [6] {a} - \ sqrt [6] {b}} = \ sqrt [6] {a} + \ sqrt [6] {b}